Pengaruh Media Audio Visual Untuk Meningkatkan Ketrampilan Shooting Pada Permainan Sepak Bola - Mu’at Kholilur Rohman; Maftukin Huda; Setiyawan Setiyawan (Jurnal Porkes, 2026)
Mu’at Kholilur Rohman is titled "The Influence of Audio-Visual Media on Improving Soccer Shooting Skills among Fourth-Grade Students at SD Negeri 1 Banyumanis." The study is motivated by the fact that shooting is a fundamental soccer technique. Preliminary observations at SD Negeri 1 Banyumanis revealed that the majority of fourth-grade students still struggled to execute the shooting technique correctly. It was anticipated that audio-visual media would help students better understand the movement stages involved in the shooting technique. This study employed Classroom Action Research (CAR) methodology. The research instruments used included observation sheets and student performance assessment sheets, while the data analysis technique employed was descriptive qualitative analysis. The results demonstrated an improvement in students' shooting skills from Cycle I to Cycle II. In Cycle I, out of 10 students, 6 (60%) were deemed to have achieved mastery according to Collaborator I, and 6 (60%) according to Collaborator II. In Cycle II, a significant improvement was observed, with 8 students (80%) achieving mastery according to Collaborator I and 8 students (80%) according to Collaborator II.